American Cutaneous Leishmaniasis: A Polymorphic Disease - De Dominicis, Charles Name (2018)
Due to the worldwide importance of this theme, we present a case of American cutaneous leishmaniasis in a 65-year- -old patient with restricted skin involvement, despite its long evolution (> 3 years). It was a difficult case to diagnose due to the atypical clinical presentation (large ulcer) and inconclusive histopathological study in the initial biopsies. The third biopsy with careful observation and the contribution of an immunohistochemical study allowed a correct diagnosis and cure after 30 administrations of N-methylglucamine antimoniate ev.